14C-AMS TECHNOLOGY AND ITS APPLICATIONS TO AN OIL FIELD TRACER EXPERIMENT. Issue 5 (11th October 2022) - Shen, Hongtao; Shi, Shulin; Tang, Junsen; Qi, Mingli; Wei, Siyu; Sasa, Kimikazu; Liu, Mingji; Wang, Li; Zhang, Guofeng; Qi, Linjie; Chen, Dingxiong; Gong, Shanhua; et al.
ABSTRACT: Many waterflooding oil fields, injecting water into an oil-bearing reservoir for pressure maintenance, are in their middle to late stages of development. To explore the geological conditions and improve oilfield recovery of the most important well group of the Hu 136 block, located on the border areas of three provinces (Henan, Shandong, and Hebei), Zhongyuan Oilfield, Sinopec, central China, a 14 C cross-well tracer monitoring technology was developed and applied in monitoring the development status and recognize the heterogeneity of oil reservoirs. The tracer response in the production well was tracked, and the water drive speed, swept volume of the injection fluid were obtained. Finally, the reservoir heterogeneity characteristics, such as the dilution coefficient, porosity, permeability, and average pore-throat radius, were fitted according to the mathematical model of the heterogeneous multi-layer inter-well theory. The 14 C-AMS technique developed in this work is expected to be a potential analytical method for evaluating underground reservoir characteristics and providing crucial scientific guidance for the mid to late oil field recovery process.